2016
DOI: 10.21511/ppm.14(1-1).2016.02
|View full text |Cite
|
Sign up to set email alerts
|

The development of disability-related employment policies in the South African public service

Abstract: AUTHORSBrian Kwazi Majola Rubby Dhunpath ARTICLE INFOBrian Kwazi Majola and Rubby Dhunpath (2016). The development of disabilityrelated employment policies in the South African public service. Problems and Perspectives in Management, 14(1-1), 150-159. AbstractWorldwide, the employment of people with disabilities has been challenged by the slow development of 'workplace specific' disability employment policies. The focus has been on formulating legislation to overcome barriers and the implementation of national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…While non-disabled students generally find part-time employment in industries that typically employ students such as restaurants and shops, students with disabilities find it difficult to obtain part-time employment, either because of transport challenges or because of the physical nature of part-time work. A study by Majola and Dhunpath (2016) highlights the difficulty that people with disabilities face when they seek gainful employment. Most students were thus dependent on their parents for their everyday expenses as well as for the more expensive items.…”
Section: Findings and Discussion: Parental Support And ‘Forms Of Capimentioning
confidence: 99%
“…While non-disabled students generally find part-time employment in industries that typically employ students such as restaurants and shops, students with disabilities find it difficult to obtain part-time employment, either because of transport challenges or because of the physical nature of part-time work. A study by Majola and Dhunpath (2016) highlights the difficulty that people with disabilities face when they seek gainful employment. Most students were thus dependent on their parents for their everyday expenses as well as for the more expensive items.…”
Section: Findings and Discussion: Parental Support And ‘Forms Of Capimentioning
confidence: 99%
“…Similarly, Shim et al (2010) showed that employed youths were likely to be more financially literate than non-employed youths. People with disabilities, especially adolescents or young adults, often rely on their parents for assistance and have limited involvement in the labor market (Goodman et al, 2017; Majola & Dhunpath, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%